Recruiters’ lived experiences in COVID-19 vaccine trials in eThekwini, KwaZulu-Natal - Dewrance, Kumari; Singh, Shenuka (Health SA = SA Gesondheid, 2025)
Background: The coronavirus disease 2019 (COVID-19) pandemic led to widespread COVID-19 vaccine trials globally, with South Africa hosting many of these studies. Participant recruitment for these trials has been hindered by vaccine hesitancy, misinformation, distrust and pandemic-related restrictions. Aim: This study explored the experiences and perceptions of recruiters involved in COVID-19 vaccine trials in eThekwini, KwaZulu-Natal, focusing on recruitment facilitators, barriers and strategies. Setting: Six clinical trial sites in eThekwini, KwaZulu-Natal. Methods: Using a qualitative phenomenological approach within an interpretive paradigm, researchers conducted in-depth online interviews via Microsoft Teams with 14 recruiters selected through non-probability purposive sampling. Field notes supplemented the interviews, and thematic analysis with open coding identified key themes. Results: Analysis of recruiters’ lived experiences revealed four main themes: (1) motivations driving participation, (2) barriers faced in the field, (3) strategies used to engage communities and facilitate enrolment and (4) recruiters’ insights for improving future recruitment success. Conclusion: This study identified the difficulties recruiters faced in enrolling participants in COVID-19 vaccine trials in eThekwini, and the reasons why participants chose to take part. Insights from recruiters can inform strategies to strengthen participant recruitment in future clinical trials. Contribution: This research provides context-specific recommendations for improving recruitment during public health emergencies, with implications for future trials in similar settings.